2023
DOI: 10.3389/fnut.2023.1101048
|View full text |Cite
|
Sign up to set email alerts
|

Defining postnatal growth failure among preterm infants in Indonesia

Abstract: BackgroundPostnatal growth failure (PGF) frequently occurred among preterm infants with malnutrition. The decline in a weight-for-age z-score of ≥1.2 has been proposed to define PGF. It was unknown whether this indicator would be useful among Indonesian preterm infants.MethodsInfants of <37 weeks of gestational age born between 2020 and 2021, both stable and unstable, were recruited for a prospective cohort study during hospitalization in the level III neonatal intensive care unit at the Cipto Mangunkus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…One study examining ELBW and very preterm infants utilizing these definitions did not find differences in neurodevelopmental outcomes on the BSID-II at 12 months ( 1 ). In contrast, one study found a decline in weight z-score > 1.2 to be associated with increased days to oral feeding ( 21 ), a known strong predictor of neurodevelopmental outcomes, and another found a weight z-score change > 1 to be associated with BSID-III scores ( 22 ). Other studies are similar to ours, identifying poor linear growth as detrimental to cognitive and language outcomes ( 8 , 15 , 23 ).…”
Section: Discussionmentioning
confidence: 96%
“…One study examining ELBW and very preterm infants utilizing these definitions did not find differences in neurodevelopmental outcomes on the BSID-II at 12 months ( 1 ). In contrast, one study found a decline in weight z-score > 1.2 to be associated with increased days to oral feeding ( 21 ), a known strong predictor of neurodevelopmental outcomes, and another found a weight z-score change > 1 to be associated with BSID-III scores ( 22 ). Other studies are similar to ours, identifying poor linear growth as detrimental to cognitive and language outcomes ( 8 , 15 , 23 ).…”
Section: Discussionmentioning
confidence: 96%
“…Brinkis et al examining ELBW and very preterm infants utilizing these definitions did not find differences in neurodevelopmental outcomes on the BSID-II at 12 months [ 1 ]. In contrast, Rohsiswatmo et al found a decline in weight z-score >1.2 to be associated with increased days to oral feeding [ 24 ], a known strong predictor of neurodevelopmental outcomes, and Yitayew et al found a weight z-score change >1 to be associated with lower BSID-III scores [ 25 ]. Other studies identify poor linear growth as detrimental to cognitive and language outcomes [ 8 , 15 , 17 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the incidence of EUGR was 71.6% (237/331) based on the definition of EUGR as a decline in weight z-score >1.2 from birth to discharge, using the Fenton growth chart 16,17) . The incidence of EUGR was higher than previous studies involving VLBW infants 2,8) , and similar to a study involving extremely preterm infants 9) .…”
Section: Discussionmentioning
confidence: 99%
“…To quantify postnatal growth, the difference in z-scores between birth and discharge was calculated. EUGR was defined as a decline in the weight-for-age z-score >1.2 from birth to discharge, using the Fenton growth chart 16,17) . The enrolled infants were categorized into an EUGR group or a non-EUGR group.…”
Section: Data Collection and Analysismentioning
confidence: 99%